(untitled) (Journal of Sciences & Technology, 2018)
In this study, the electrochemical decolorization of the Methylene Blue dye on Platinum electrodes was assessed. Direct oxidation results demonstrate a partial pollutant degradation reaching a maximum of 64 %. However, the addition of a small amount of a redox mediator Co2+/3+ is efficiently able to electrocatalyse the Methylene blue oxidation by shortening significantly the treatment time and enhancing clearly the dye decolorization rate. Nearly complete decolorization was achieved (92 % in 1h 45min). The most striking results achieved within the cyclic voltammetry study demonstrate undoubtedly the pollutant mineralisation. Electrochemical experiments were performed using the spectrophotometric method, which is very convenient, easy and allows monitoring the spectral changes as well as the determination of the dye concentration during the process. The kinetics data show a first-order indirect oxidation kinetics. A mechanism was proposed to explain the different phenomenon during the electrochemical process.